2015
DOI: 10.1208/s12249-015-0391-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Bioavailability and Pharmacodynamic Effects of Thymoquinone Via Nanostructured Lipid Carrier (NLC) Formulation

Abstract: Abstract. Thymoquinone (TQ), obtained from black cumin (Nigella sativa), is a natural product with antioxidant, anti-inflammatory, and hepatoprotective effects but unfortunately with poor bioavailability. Aiming to improve its poor oral bioavailability, TQ-loaded nanostructured lipid carriers (NLCs) were prepared by high-speed homogenization followed by ultrasonication and evaluated in vitro. Bioavailability and pharmacodynamic studies were also performed. The resultant NLCs showed poor physical homogeneity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 32 publications
3
54
0
Order By: Relevance
“…of TQ have been identified that are somehow involved in tumorigenesis or development of drug resistance (Kundu et al, 2014b) (Figure 1). Though treatment with TQ alone has shown antitumor efficacy in several in vitro and in vivo studies as mentioned in details in a recent review (Majdalawieh et al, 2017), the lower efficacy (Effenberger et al, 2010) and poor bioavailability (Ganea et al, 2010; Elmowafy et al, 2016) of TQ is the primary bottleneck for considering it as the primary therapeutic agent. Therefore, in this review, we proposed the potential role of TQ as an adjuvant therapy with different types of conventional cancer treatments namely surgery, radiotherapy, chemotherapy, and immunotherapy either to prevent carcinogenesis or to potentiate the efficiency of conventional therapeutic modalities.…”
Section: Introductionmentioning
confidence: 99%
“…of TQ have been identified that are somehow involved in tumorigenesis or development of drug resistance (Kundu et al, 2014b) (Figure 1). Though treatment with TQ alone has shown antitumor efficacy in several in vitro and in vivo studies as mentioned in details in a recent review (Majdalawieh et al, 2017), the lower efficacy (Effenberger et al, 2010) and poor bioavailability (Ganea et al, 2010; Elmowafy et al, 2016) of TQ is the primary bottleneck for considering it as the primary therapeutic agent. Therefore, in this review, we proposed the potential role of TQ as an adjuvant therapy with different types of conventional cancer treatments namely surgery, radiotherapy, chemotherapy, and immunotherapy either to prevent carcinogenesis or to potentiate the efficiency of conventional therapeutic modalities.…”
Section: Introductionmentioning
confidence: 99%
“…This study was designed for quantification and evaluation of pharmacokinetics of TQ in layer chickens following PO and IV administration. The PO dose was selected according to previous study in rats (Elmowafy et al, ) while IV dose was established based on study conducted in rabbits (Alkharfy et al, ). For this purpose, a sensitive and selective HPLC system was utilized for pharmacokinetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed for quantification and evaluation of pharmacokinetics of TQ in layer chickens following PO and IV administration. The PO dose was selected according to previous study in rats (Elmowafy et al, 2016) Khan, & Alkharfy, 2015). In this study, a combination of sodium di-hydrogen phosphate buffer and acetonitrile was utilized as mobile phase.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute oral bioavailability of both DIM-10 and DIM-14 was found to be approximately <20%. Because many studies demonstrated the promising role of different nanoformulations in overcoming poor aqueous solubility [25,31,5,28], we chose NLC formulation approach [17,32,6,24]. Initially, prepared NLC formulation were subjected to in vitro drug release profiles and found that both DIM-10 and DIM-14 release were significantly increased in NLC formulations compared to free drugs; this increased drug release is due to increase solubility of DIMs in nanocarrier systems.…”
Section: Discussionmentioning
confidence: 99%